Market-Economic Decentralization and Governance in Hargeisa Local Government, Somaliland - Abdillahi, Mustafe Mahamoud; Benjamin, Bella Oluka (UI Scholars Hub, 2025)
This study investigates the relationship between market-economic decentralization and governance within the Hargeisa Local Government in Somaliland. Market-economic decentralization, influenced by neoliberal principles, involves transferring decision-making authority to local levels to stimulate private sector engagement and economic efficiency. Despite comprehensive decentralization reforms initiated in 2001, Hargeisa continues to confront significant governance challenges, including institutional weaknesses, fiscal mismanagement, and corruption. Employing a mixed-methods approach, this research integrates quantitative surveys and qualitative interviews with 269 local officials to assess the impact of decentralization on key governance indicators: accountability, transparency, and e-governance. The results demonstrate strong positive correlations between market-economic decentralization and improved governance outcomes (r = 0.670–0.678, p < 0.01). Regression analysis further indicates that decentralization accounts for 60% of the variance in governance performance (β = 0.778, p < 0.001), with fiscal autonomy, public-private partnerships (PPPs), and foreign direct investment (FDI) identified as critical factors. Nevertheless, persistent obstacles such as heavy fiscal dependence (80% on central transfers), gender imbalances (60.2% male workforce), elite capture, and divergent public perceptions on privatization curtail the full potential of decentralization. These findings resonate with the Soufflé Theory, emphasizing the need for balanced political, fiscal, and administrative integration, and the Principal-Agent Theory, which highlights accountability gaps. The study concludes that while decentralization enhances governance, its efficacy is moderated by contextual and institutional factors. It advocates for complementary strategies, including capacity building, gender-inclusive policies, transparent investment frameworks, and digital governance, to maximize decentralization benefits in fragile states like Somaliland.